Yield of Formyl Radical from the Vinyl + O2 Reaction. Issue 5 (9th October 2013) - Matsugi, Akira; Miyoshi, Akira
ABSTRACT The yield of formyl (HCO) radical from the reaction of vinyl (C2H3) radical with O2 has been investigated by using a pulsed laser photolysis/cavity ring‐down spectroscopy technique at room temperature. The rate constants for the C2H3 + O2 and HCO + O2 reactions were measured to be (8.60 ± 0.87) × 10−12 and (5.55 ± 1.00) × 10−12 cm3 molecule−1 s−1, respectively, which were consistent with preceding studies. The yield of HCO radical was determined to be ϕ(HCO) = 0.222 ± 0.066, and it was independent of pressure in the pressure range 10–100 Torr with He or N2 buffer. The Rice–Ramsperger–Kassel–Marcus calculation combined with a prior energy distribution model could reproduce the experimental HCO‐radical yield and indicated that a significant portion of HCO radicals formed in the C2H3 + O2 reaction promptly dissociated to H + CO. The first CO‐stretch excited state of HCO radical, HCO(0, 0, 1), was observed at the total pressure of 1 Torr; the time profiles of which were satisfactory reproduced by a kinetic simulation including the relaxation of hot HCO radicals. These experimental, theoretical, and modeling results provide solid evidence for the prompt dissociation of hot HCO radicals formed in the C2H3 + O2 reaction. The product‐specific rate constants that extrapolated to higher temperature and wider pressure ranges are presented. Implications of the suggested mechanism for combustion modeling are also discussed.